PERTIMBANGAN HAKIM TERHADAP PELAKU TINDAK PIDANA PENGANIAYAAN DALAM KEADAAN MABUK YANG MENGAKIBATKAN LUKA BERAT (Studi Putusan Nomor : 41/Pid.B/2024/PN Met) - Muhammad Ronald Dzaky Al Zabbar; Erlina Bachri (INTELIGENSIA MEDIA, 2025)
This study aims to analyze the causal factors of the occurrence of criminal acts of assault while intoxicated resulting in serious injuries based on decision No: 41/Pid.B/2024/PN Met and the Judge's considerations in issuing a verdict on the criminal act of Assault While Intoxicated Resulting in Serious Injuries based on decision No: 41/Pid.B/2024/PN Met. The research method used is normative juridical using an Empirical Approach. Data collection techniques with literature studies, legal principles and applicable laws and regulations, observation and interviews. The results of the study indicate that the causal factors of the occurrence of criminal acts of assault while intoxicated resulting in serious injuries based on decision No: 41/Pid.B/2024/PN Met are: elements that cause the occurrence of criminal acts of assault under the influence of alcohol resulting in material losses, as stated in Decision No. 41/Pid.B/2024/PN Met. The abuse occurred because the defendant and the victim were drunk, there was an argument, loss of self-control and intense emotions which resulted in abuse in the form of stabbing using a sharp weapon which caused the stab to hit the victim's body. Furthermore, the discussion of the research on the Judge's considerations in passing a verdict on the crime of Abuse While Drunk Resulting in Serious Injuries based on decision No: 41 / Pid.B / 2024 / PN Met, namely: The judge's considerations in determining the defendant's criminal liability are based on the facts found during the trial and applicable criminal norms, taking into account the factors of culpa and mens rea involved in the actions of the defendant who was legally and convincingly proven guilty of committing the crime of abuse resulting in very large losses.